A study on work stress that influence work life balance: discussion / Aini Qamariah Mohd Yusof ... [et al.] - Mohd Yusof, Aini Qamariah; Md Razak, Mohamad Idham; Osman, Shahariah; Md Ghazal, Raihan (2014)
Work stress has becomes a common problem that faced by employees in many organizations regardless any industry that they involves today. Work-life balance and stress go hand in hand. What seems to matter in this regard is the importance workers place on balance in their lives and the effectiveness of work place policies and practices in supporting them to achieve this goal. This paper focuses on the work life of both employers and employees’ and also suggests how work life-balance has to be achieved. The employers needs to frame polices that would minimize the work load of employee without affecting the productivity of the organisation, for achieving successful work-life balance. Workload, role conflict and interpersonal relationship at work are the factors that the researcher emphasized in this study. The researches need to find out what are the relationships these factors with stress as well as affecting work life balance. 80 of questionnaires were distributed randomly as a sample and the technique that will be used is convenient sampling technique in order to get relevant and significant data.